Subtract the following polynomials, then place the answer in the proper location on the grid. write the answer in descending powers of a.
subtract: 11a2 + 42a - 6 from 14a 2 - 24a + 7.
( a + b )^3 = a^3 +b^3 +3 a²b +3b²a + *)
the condition is : r = 1 and p=1
put : x= a and b = 1 in (*) you have :
(x + 1)^3 = x^3 +3x² +3x +1
the zeros is : x = - 1
bcause : x^3 +3x² +3x +1 = 0 (x + 1)^3 = 0 so : x = - 1
answer: (25,45) has the same solution
i did it on a piece of paper i would take a pic and show u but rn i'm on computer